2012
DOI: 10.1007/s12264-012-1058-4
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of microglia and interleukin-18 in the induction of long-term potentiation of spinal nociceptive responses induced by tetanic sciatic stimulation

Abstract: Immunohistochemistry showed that minocycline inhibited the sequential activation of microglia and astrocytes, and IL-18 was predominantly colocalized with the microglial marker Iba-1 in the spinal superficial dorsal horn. Western blot revealed that repeated intrathecal injection of minocycline significantly inhibited the increased expression of IL-18 and IL18Rs in microglia induced by TSS. Conclusion The IL-18 signaling pathway in microglia is involved in TSS-induced spinal LTP and mechanical allodynia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 51 publications
1
16
0
Order By: Relevance
“…Some published data showed that administration of IL-18 leads to increased microglial activation (Prinz and Hanisch, 1999). Studies suggest that IL-18 released by microglial cells is responsible for the development of allodynia (Miyoshi et al, 2008;Chu et al, 2012;Daigo et al 2012), which is consistent with our results. On day 7 following CCI, the IL-18 mRNA levels in the spinal cord and DRG increase and are reduced by minocycline administration.…”
Section: Discussionsupporting
confidence: 93%
“…Some published data showed that administration of IL-18 leads to increased microglial activation (Prinz and Hanisch, 1999). Studies suggest that IL-18 released by microglial cells is responsible for the development of allodynia (Miyoshi et al, 2008;Chu et al, 2012;Daigo et al 2012), which is consistent with our results. On day 7 following CCI, the IL-18 mRNA levels in the spinal cord and DRG increase and are reduced by minocycline administration.…”
Section: Discussionsupporting
confidence: 93%
“…IL-18 is highly related to IL-1β, and both require caspase-1 and inflammasomes for active cleavage[146]. Nerve injury induces IL-18 expression in spinal microglia[34,167]. Furthermore, painful injuries induce cytokine expression in peripheral glia.…”
Section: Different Activation States Of Glia After Painful Stimulimentioning
confidence: 99%
“…It was subsequently reported that the inhibitory effect of IL-18 on LTP could be attenuated by the mGluR5 specific antagonist MPEP and the group II mGluR antagonist, MTPG (Cumiskey et al, 2007c) and also by the COX-2 inhibitor, SC-236, the iNOS inhibitor 1400W and peroxisome proliferation activated receptor (PPAR)γ agonist, ciglitazone (Cumiskey et al, 2007b). Interestingly IL-18 also inhibits LTP of C-fiber-evoked field potentials induced by tetanic stimulation of the sciatic nerve in the spinal cord and the authors identified a key role for microglial activation since IL-18 was localized largely to microglia and this effect was inhibited by minocycline (Chu et al, 2012).…”
Section: Il-1β Il-18 the Inflammasome And Ltpmentioning
confidence: 99%